INSTITUTES OF APPEAL IN THE SYSTEM OF ADMINISTRATIVE JUSTICE - Kaizhakparova , Аида Бахытжановна; Ermekbayev, Берикжан Бакытжанович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2018)
The reform of administrative law involves the need to introduce administrative justice that resolves disputes arising from public law relations between the state and citizens (organizations), which is stipulated by the Concept of Legal Policy of the Republic of Kazakhstan for the period from 2010 to 2020, approved by Decree of the President of the Republic of Kazakhstan. An important strategic document is the Decree of the President of the Republic of Kazakhstan “On Approval of the Strategic Development Plan of the Republic of Kazakhstan until 2025 dated February 15, 2018,” which noted a positive trend in reforming the judicial system, in particular, reducing the time for consideration of cases, an increase in the number of cases resolved using simplified legal proceedings and alternative dispute resolution measures. From this it follows that it is necessary to develop in every way the methods that have proven themselves widely in the world: pre-trial and judicial settlement of disputes through negotiations, settlement agreements, as well as alternative ways of resolving public disputes. The main purpose of improving the institute of pre-trial appeal, in addition to the unloading of courts, is to increase the level of responsibility of state bodies in making decisions, administrative acts, their officials for their actions (inaction), the need for protection from government interference. This article examines and analyzes the regulatory legal acts governing the institution of appeal in general, and the institution of pre-trial settlement of public disputes in particular. The characteristic and classification of institutions of appeal, including: intradepartmental, extradepartmental and judicial. The main stages of appeal, as well as the powers of state bodies in appealing acts, decisions of state authorities (actions and inactions of officials), as the main participants in public relations, are considered.